Value of TCT combined with HPV and CA125 in early cervical cancer screening in a medical examination population: Value of TCT combined with HPV and CA125 - Xiao, Meiping; Zhang, Zhiying; Yu, Xiaohong; Fan, Yinbai; Chen, Xuehong (Cellular and Molecular Biology, 2022)
This research aimed to explore the clinical value of thin prep cytologic test (TCT) combined with human papillomavirus (HPV) and carbohydrate antigen 125 (CA125) in early cervical cancer screening in the physical examination population. For this purpose, a total of 3587 females who received gynecological physical examination in the outpatient department of Ganzhou people's Hospital from January 2018 to March 2022 were included and underwent TCT, HPV and carbohydrate antigen 125 upon admission. Colposcopy biopsy was performed on patients who tested positive for any of the three indicators. Then using pathological diagnosis as the gold standard, the three methods applied alone or in combination were evaluated in terms of sensitivity, specificity, diagnostic yield and Youden index. Results showed that Among the 3587 females, 476 (13.27%) were HPV positive, 364 (10.14%) CA125 positive, and 314 (8.75%) TCT positive. Furthermore, 738 tested positive for any of the three indicators and underwent cervical biopsy. Among the 738 cases, 280 (39.94%) developed chronic cervicitis, 268 (36.31%) low-level cervical intraepithelial neoplasia (CIN), 173 (23.44%) high-level CIN, and 17 (2.30%) cervical cancer. HPV+TCT+CA125 combined screening showed higher sensitivity (94.54%), specificity (83.92%), diagnostic coincidence rate (87.46%) and Youden index (0.760) than single-indicator examinations. Also, it had the largest area under the receiver operating characteristic (ROC) curve, 0.673 (0.647, 0.699), compared to any other screening method. In conclusion, The combined detection of CA125, HPV and TCT is of clinical significance due to its higher sensitivity and accuracy in early screening of cervical cancer in the physical examination population.